2006
DOI: 10.1007/s00066-006-1543-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hemoglobin Levels on Tumor Oxygenation: the Higher, the Better?

Abstract: Review of relevant clinical data suggests that a maximum oxygenation status in solid tumors is to be expected in the range 12 g/dl < cHb < 14 g/dl for women and 13 g/dl < cHb < 15 g/dl for men. Considering the "optimal" cHb range with regard to tumor oxygenation, the concept of "the higher, the better" is therefore no longer valid. This finding has potentially far-reaching implications in the clinical setting (e. g., inappropriate erythropoietin treatment of nonanemic tumor patients).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 84 publications
3
73
3
1
Order By: Relevance
“…However, the treatment programs used in the SCOPE1-trial for definitive treatment appeared not optimal. The radiation dose appeared relatively low and induction chemotherapy may have led to anemia and subsequent tumor hypoxia, which is known to impair the effect of radiotherapy (29). In contrast to the SCOPE1-trial, the preliminary results of a randomized phase II study showed a better progressionfree survival (PFS) in patients receiving cetuximab in addition to radio-chemotherapy (27).…”
Section: Definition Of Dose Limiting Toxicities (Dlts)mentioning
confidence: 99%
“…However, the treatment programs used in the SCOPE1-trial for definitive treatment appeared not optimal. The radiation dose appeared relatively low and induction chemotherapy may have led to anemia and subsequent tumor hypoxia, which is known to impair the effect of radiotherapy (29). In contrast to the SCOPE1-trial, the preliminary results of a randomized phase II study showed a better progressionfree survival (PFS) in patients receiving cetuximab in addition to radio-chemotherapy (27).…”
Section: Definition Of Dose Limiting Toxicities (Dlts)mentioning
confidence: 99%
“…Several experimental studies suggest that anemia leads to a higher degree of hypoxia (13,14) in tumor than would be expected for nonneoplastic tissues. Low levels of tissue oxygen tension (pO 2 ) induce cell signaling through the AKT-mammalian target of rapamycin, thus leading to the up-regulation of hypoxia-inducible factor 1a.…”
mentioning
confidence: 99%
“…In addition, high haemoglobin levels predispose to pathologic clot formation. Haemoglobin levels must be 12-14 g/dl in women and 13-15 g/dl in men to achieve optimal tumour oxygenation and the best results from radiotherapy [5]. Th ese data have been confi rmed in a retrospective study of 108 oesophageal cancer patients, where haemoglobin levels during radiotherapy of 12-14 g/dl resulted in better 2-year loco-regional control than levels <12 g/dl or >14 g/dl (58% vs. 19% and 44%, p < 0.001) [6].…”
Section: Introductionmentioning
confidence: 99%